The Effect of Using Observe and Remember Game in Mastering Vocabulary English Students at the Second Grade of SMPN 1 Harau - Dialestari, Rona; Syahrul, Syahrul; Dewi, Merry Prima; Safitri, Loli (Darul Yasin Al Sys, 2023)
The vocabulary mastery of English students at the 2nd grade of SMP N 1 Harau was often constrained by the problem of the lack of students’ ability to remember vocabulary. Students had little vocabulary and they thought English was difficult to learn. The researcher tries to offer a strategy for teaching vocabulary by using